A Collaborative Data Network for the Asia Oceania Region Enabled by Emerging Technologies to Foster Innovation in a Secure and Open Environment - Alison Specht; Kim Bryceson; Shoufeng Cao; Margaret O’Brien; S. M. Guru; Pedro Pizzigatti Correa; Michelle Waycott (Data Science Journal)
A discoverable inventory of items of value and importance to a community, country, or region has many benefits. These benefits can be for reporting (state of the environment, achievement of Sustainable Development Goals, conservation objectives), for research (exploration of international phylogenetics, development of new pharmaceuticals), or for economic reasons. Confidence in the value of data is best achieved if the information used to underpin statements and conclusions is open to scrutiny. This paper presents a framework for the creation of a collaborative data network for the Asia-Oceania region that will allow members to hold, manage, and share data about their countries and regions. We propose a ‘Collaborative Regional Data Access Network’ (CREDAN) that will blend the attributes of centralised and decentralised networked databases for the management and discovery of data. Following the CARE principles, data owners will determine the sovereignty and sharing permissions for their data. To ensure ownership is always clear, and subsequent use of data is tracked, we harness blockchain technology alongside smart contracts and decentralised identifiers to allow secure discovery and sharing. The use of blockchain will ensure the information about each dataset (metadata, provenance, and access rights) is immutably connected to each dataset. We recommend a strong governance structure to ensure best practices are aligned with international criteria and those set by the component communities. Management of the eventual large volume of data should be anticipated, and partnerships may need to be considered. We propose a seven-step pathway to creation of such a network.